Enhancing Digital Literacy and Computational Thinking through Scratch-Based Learning - Dinar Munggaran Akhmad; Ersa Resita; Hutagalung, Carli Apriasnyah; Gustian Rama Putra; Hylmi Akhdan (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2025)
In the digital era, students must develop digital literacy and computational thinking skills to face technological challenges. However, many Indonesian schools still emphasize theoretical knowledge rather than practical applications. This community service program aimed to enhance these skills through Scratch-based learning at the Muslihun Foundation, Parung, Bogor Regency. The program involved 21 junior and senior high school students and was implemented in five stages: preparation, socialization, Scratch training, project mentoring, and evaluation. Using a Project-Based Learning (PjBL) approach, students learned to create animations and educational games that applied computational concepts creatively. The evaluation used a 10-item pre-test and post-test instrument measuring basic digital literacy, logic, sequencing, and problem-solving indicators. The average score increased from 62.86 to 98.10, representing a 56% enhancement. Most participants achieved perfect post-test scores, proving the effectiveness of Scratch-based learning in improving computational thinking, creativity, and engagement. These findings highlight the need for accessible hands-on digital learning models and demonstrate the potential of simple visual programming tools to strengthen inclusive digital education practices in Indonesia.